Evaluation of the impact of the Spanish Consensus Document on the approach to osteoarticular infections in Spain through the Paediatrics Osteoarticular Infections Network (RIOPED) - Esmeralda Núñez Cuadros; Cristina Calvo; Jesús Saavedra-Lozano; Rosa Alcobendas Rueda; Daniel Clemente Garulo; F. José Sanz Santaeufemia; Leticia Martínez Campos; Alfredo Tagarro García; César G. Fontecha; Susana Melendo-Pérez; Marisol Camacho Lovillo; Lola Falcón Neyra; et al. (Elsevier, 2020)
Introduction: In 2014 the Consensus Document produced by the Spanish Paediatric Societies (SEIP-SERPE-SEOP) was published to help in the diagnosis and treatment of osteoarticular infections (OAI). In 2015 the RIOPed was considered as a multidisciplinary national network for the investigation into OAI. The aim of this study was to assess the level of adaption to the recommendations established in the Consensus during one year of follow-up. Material and methods: A prospective, national multicentre study was carried out in 37 hospitals between September 2015 and September 2016. The study included patients >16 years-old with a diagnosis of OAI, confirmed by microbiological isolation, or probable: septic arthritis (SA) with >40,000 white cells in synovial fluid, or osteomyelitis (OM)/spondylodiscitis (SD) with a compatible imaging test. The results were compared with those obtained in a retrospective study conducted between 2008 and 2012. Results: A total of 235 cases were included, of which 131 were OM, 79 SA, 30 OA, and 15 SD. As regards the complementary tests that the Consensus considered mandatory to perform, radiography was carried out on 87.8% of the cases, a blood culture on 91.6%, and culture of the synovial fluid in 99% of SA. A magnetic resonance (MR) was performed on 71% of the OM cases. The choice of intravenous empirical antibiotic treatment was adapted to the recommendations in 65.1% of cases, and in 62.3% for the oral treatment. Surgery was performed in 36.8% of SA cases (85.7% arthrotomy), with a significant decrease compared to the retrospective study (P = .014). Only 58.5% of cases followed the recommendations on the duration of the treatment; however, a lower duration of intravenous treatment was observed. Conclusions: In general, the level of adaptation to the recommendations that were set by the Expert Group, is good for the complementary tests, and acceptable as regards the choice of antibiotic treatment, although inadequate in almost 40% of cases. A decrease in hospital stay was achieved. Resumen: Introducción: En 2014 se publicó el Documento de Consenso desarrollado por SEIP-SERPE-SEOP para el diagnóstico y el tratamiento de las infecciones osteoarticulares (IOA). En 2015 se constituyó RIOPed como red nacional multidisciplinar para la investigación en IOA. El objetivo del estudio ha sido valorar el grado de adecuación a las recomendaciones establecidas en el consenso durante un año de seguimiento. Material y métodos: Estudio prospectivo multicéntrico nacional realizado entre septiembre de 2015 y septiembre de 2016 en 37 hospitales con inclusión de pacientes menores de 16 años diagnosticados de IOA, confirmada mediante aislamiento microbiológico, o probable: artritis séptica (AS) con >40.000 leucocitos en líquido sinovial u osteomielitis (OM)/osteoartritis (OA)/espondilodiscitis (ED) con prueba de imagen compatible. Los resultados se compararon con los obtenidos en el estudio retrospectivo realizado entre 2008 y 2012. Resultados: Se incluyeron 255 casos: 131 OM, 79 AS, 30 OA y 15 ED. Respecto a las pruebas complementarias que el consenso consideró de obligada realización, la radiografía se llevó a cabo en el 87,8% de los casos, el hemocultivo en el 91,6% y el cultivo de líquido sinovial en el 99% de AS. Se realizó RM en el 71% de las OM. La elección del tratamiento antibiótico intravenoso empírico se adecuó a las recomendaciones en el 65,1% de los casos, y en el 62,3% para el tratamiento oral. Se llevó a cabo cirugía en el 36,8% de las AS (85,7% artrotomía), con un descenso significativo respecto al estudio retrospectivo (P = ,014). Solo el 58,5% de casos se ajustaron a las recomendaciones de duración del tratamiento; sin embargo, se comprobó una menor duración del tratamiento intravenoso. Conclusiones: En general, el grado de adecuación a las recomendaciones que marcaron el grupo de expertos es bueno para las pruebas complementarias y aceptable respecto a la elección del tratamiento antibiótico, aun detectándose casi un 40% de inadecuación. Se ha conseguido un descenso de la estancia hospitalaria.